Estimation of daily solar radiation for the city of Bagua, Amazonas region, Perú - Quiñones H., Lenin (2019)
The solar radiation that reaches the earth is the fundamental source of renewable energy in nature, therefore, knowing the local solar radiation is essential for many applications. The objective of this study was to model the behavior of daily solar radiation in the city of Bagua, which allows us to plan and design strategies oriented towards the use of the primary source of renewable energy. For this, the Fernández-Zayas model has been used, which considers the parameters of the monthly  average of the maximum global solar radiation and the length of the solar day. The methodology is of the analytical type and consisted of three phases: The first, data collection and filtering of the meteorological station of the Toribio Rodríguez de Mendoza National University of Amazonas that is located in the study area; in the second, the model was implemented using the MATLAB / GUI interface, obtaining the simulation of solar radiation; and in the third, the model was validated by error goodness statistics and table t. The estimate of daily solar radiation was calculated and discussed. The results obtained are useful for any application of solar energy in the city of Bagua, Amazonas region, Peru.